Minimally invasive approaches using virtual reality planning in elective aneurysm surgery - Greuter, Ladina; Stoessel, Tabea; Ebel, Florian; Westarp, Emilia; Saemann, Attill; Rychen, Jonathan; Cattin, Philippe; Zelechowski, Marek; Faludi, Balasz; Soleman, Jehuda; Guzman, Raphael (Frontiers in Surgery, 2025)
IntroductionWhile endovascular treatment has gained popularity for its minimally invasive approach, microsurgical clipping for unruptured intracranial aneurysms (UIAs) has also evolved using surgical adjuncts such as virtual reality (VR) and keyhole techniques to enhance patient outcomes. Immersive 3D VR images allow for the creation of an accurate 3D anatomical model, making it a valuable tool for surgical planning. This study investigated the impact of VR-based surgical planning on approach type and craniotomy size.MethodsThis retrospective cohort study included all patients who underwent elective microsurgical clipping for UIAs from 1 January 2009 to 31 December 2024 at the University Hospital of Basel, Switzerland, and was approved by the local ethics board. Demographic, surgical, and outcome parameters were collected. SpectoMedical®, developed at the University of Basel, was the VR platform used. The primary outcome was craniotomy size (cm2) measured using the anterior-posterior method. Descriptive and comparative statistics were conducted. To assess the factors influencing the craniotomy size, we calculated a multivariable linear regression model.ResultsWe included a total of 163 aneurysms in 159 patients with a mean age of 58.52 (±10.23), and 114 (69.9%) were female. VR-based surgical planning resulted in a significantly smaller craniotomy size [no VR vs. VR, 20.31 (±19.21) cm2 vs. 13.22 (±7.85) cm2, p = 0.007] and shorter hospital stay [no VR vs. VR, 10.04 (±5.58) vs. 7.89 (±2.79) days, p = 0.031]. Operative time was shorter in the VR group but lacked statistical significance [no VR vs. VR, 226.41 (±86.18) min vs. 207.93 (±54.92) min, p = 0.160]. The multivariable regression model showed that the use of VR-based surgical planning reduced the craniotomy size by 6.2 cm2.ConclusionVR-based surgical planning was associated with significantly smaller craniotomy sizes and shorter hospital stays. It results in an intraoperative déjà-vu effect for the surgeon, which supports its use as a valuable adjunct in preoperative planning.